2005
DOI: 10.1002/jts.20023
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic symptoms and self-dysfunction as consequences and predictors of sexual revictimization

Abstract: Posttraumatic symptomatology (PTS) and self-dysfunction (SD) were examined as correlates and predictors of sexual revictimization in a prospective study of 339 college women. Both PTS and SD were associated with a history of child and adult sexual victimization. Compared to a history of child victimization, a history of adult victimization was associated with greater self-dysfunction. Both PTS and SD predicted revictimization during the study; however, self-dysfunction also predicted victimization in the absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 30 publications
6
55
2
1
Order By: Relevance
“…First, in a 2-year, three-wave longitudinal study of a national probability sample of American women, Acierno and colleagues (1999) found that PTSD predicted ASA victimization during the subsequent 2 years, albeit only when previous victimization was not in the model. Second, in a prospective study of college women, Messman-Moore, Brown, & Koelsch (2005) found that posttraumatic symptoms assessed at Time 1 were marginally higher among previous abuse victims who were sexually revictimized within the following 8 months than among previous abuse victims who were not.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…First, in a 2-year, three-wave longitudinal study of a national probability sample of American women, Acierno and colleagues (1999) found that PTSD predicted ASA victimization during the subsequent 2 years, albeit only when previous victimization was not in the model. Second, in a prospective study of college women, Messman-Moore, Brown, & Koelsch (2005) found that posttraumatic symptoms assessed at Time 1 were marginally higher among previous abuse victims who were sexually revictimized within the following 8 months than among previous abuse victims who were not.…”
mentioning
confidence: 98%
“…The Arata (2000) and Sandberg et al (1999) studies both used the Revised Impact of Events Scale (IES; Horowitz, Wilner, & Alvarez, 1979), and the Messman-Moore et al (2005) study used several subscales from the Trauma Symptom Inventory (TSI; Briere, 1995). Both measures assess only two of the symptom clusters that currently define PTSD (intrusion and avoidance); neither assesses the third (hyperarousal) cluster.…”
mentioning
confidence: 99%
“…La relation entre les SSPT et la victimisation au sein des relations amoureuses s'expliquerait notamment par le fait que la nature des symptômes taxerait la capacité de l'individu à cerner les situations à risque et à déployer des stratégies de protection relativement à ces situations (Arata, 2000 ;Chu, 1992 ;Orcutt, Erickson et Wolfe, 2002). Un effet médiateur des SSPT a ainsi été observé dans la relation entre l'agression sexuelle dans l'enfance et la revictimisation sexuelle à l'âge adulte (Arata, 2000 ;Messman-Moore, Brown et Koelsch, 2005). Un effet médiateur réfère ici à une variable intermédiaire qui représente le mécanisme par lequel l'agression sexuelle est associée au risque de revictimisation.…”
Section: Symptômes De Stress Post-traumatiqueunclassified
“…Female college students with a history of trauma report greater frequency of engagement in risky coping strategies such as using alcohol or drugs (Corbin, Bernat, Calhoun, McNair, & Seals, 2001;Krupnick, Green, Stockton, Goodman, Corcoran, & Petty, 2004;Miranda, Meyerson, Long, & Simpson, 2002) or engaging in risky sexual behaviors such as having multiple partners (Filipas & Ullman, 2006;Green et al, 2005;Norris et al, 1996). Higher levels of PTSD symptoms have also been related to revictimization (Messman-Moore, Brown, & Koelsch, 2005). These experiences are likely to worsen their symptoms further.…”
Section: Treatment Considerations For College Students With Ptsd and Sudmentioning
confidence: 99%
“…Surveys with college students indicate that 5.2% (70 of 1,395) of college women report sexual abuse or assault by a dating partner while in college (Harned, 2004). Prospective studies of completed rape (defined as completed oral, anal, or vaginal penetration) of college women have found rates of 3.4% (over 9 weeks; Gidycz, Coble, Latham, & Layman, 1993) and 9.5% (over 8 months; Messman-Moore, Brown, & Koelsch, 2005). College students with a history of childhood sexual abuse are more likely to be victimized while in college (Gidcyz, Coble, Latham, & Layman, 1993).…”
Section: Introductionmentioning
confidence: 99%